Clear Cell Carcinoma Arising from Endometriosis at the Cesarean Scar Site: A Case Report - Kong, Mi Kyung; Jung, Hyun Joo; Kim, Yeon Hee; Kim, Jaehoon; Kim, Sunghoon (Archives of Clinical and Medical Case Reports, 2019)
The association of endometriosis with ovarian cancer has been a rare but well-documented phenomenon since 1925, when Sampson first described clear cell carcinoma arising from endometriosis. Here, we report the case of a woman who underwent staging <gwmw class="ginger-module-highlighter-mistake-type-1" id="gwmw-15755303360997891126602">laparotomy</gwmw> including total abdominal hysterectomy and bilateral salpingo-oophorectomy with the excision of an abdominal wall mass at the site of her cesarean section scar. Although the abdominal wall mass and lymph node was proven to be clear cell carcinoma, the patient’s ovaries were free of carcinoma. This case provides important etiological evidence because it is a clear example of endometriosis that has transitioned to clear cell carcinoma. We report this case for review.